Energy state and micromechanical properties of PbO-ZnO-B₂O₃ glass-ceramic functional coatings on AISI420 stainless steel substrate - Duriagina, Z.; Kovbasyuk, T.; Bialopiotrowicz, T.; Bespalov, S. (Functional Materials, 2017)
On AISI420 steel substrates with different roughness, PbO-ZnO-B₂O₃ glass crystalline functional coatings were synthesized by means of thick films method. The parameters of micro topography and values of free surface energy of the coatings and those of substrates surfaces have been investigated. The character of influence of substrates' micro topography and of free surface energy on the micromechanical properties of the synthesized coatings has been ascertained.